Clofarabine in the treatment of acute myeloid leukemia in older adults. (February 2013) - Tiley, Stephen; Claxton, David
Objective: To review the literature evaluating the efficacy and tolerability of clofarabine as a single agent and in combination therapy for older patients with acute myeloid leukemia (AML). Method: A literature search of the PubMed database (1996–April 2012) using the search terms clofarabine and acute myeloid leukemia was performed. All relevant English language articles were reviewed. Clinical trials with patients aged 50 years or older diagnosed with AML were included. Results: Two studies evaluating clofarabine as monotherapy and five studies evaluating clofarabine in combination with cytarabine were reviewed. Clofarabine demonstrated activity in older adults with AML. Response rates and median overall survival (OS) for patients receiving clofarabine were similar to those for patients receiving conventional induction chemotherapy. The induction mortality rate with clofarabine was lower than that seen with intensive chemotherapy. However, clofarabine was associated with a significant risk of severe complications including myelosuppression and sepsis. Conclusion: Clofarabine is an active agent for the treatment of older patients with AML as a single agent or in combination therapy. Based on published data and side-effect profiles, clofarabine may be an appropriate alternative to intensive chemotherapy for older patients with AML, offering similar response rates to traditional 7+3 chemotherapy with potentially decreased induction mortality. The use of clofarabine in combination with newer agents including DNA methyltransferase inhibitors like decitabine is a promising approach for older patients who are not eligible for intensive chemotherapy. Additional randomized controlled trials are needed to directly compare the efficacy of clofarabine as a single agent and in combination therapy compared with intensive chemotherapy regimens.